ANALISIS PENGARUH IPM, INFLASI, DAN TINGKAT PENGANGGURAN TERHADAP PERTUMBUHAN EKONOMI REGIONAL 6 KOTA DI PROVINSI JAWA TENGAH TAHUN 2014-2019 - Bhaskara Dhanu Kusuma (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2025)
Gross Regional Domestic Product (GRDP) is one of the indicators used to assess the economic condition of a region. This research was conducted to find out what factors affect economic growth in the six main cities of Central Java Province in the 2014-2019 time span. The data used in this study are secondary data processed from the official website of the Central Statistics Agency and are in the form of panel data. The best panel data regression model used is the regression model with random effects, with the results of the study in the form of unemployment rate and HDI variables having a significant effect on economic growth, while the inflation variable has no significant effect. This regression model is able to explain 60% of the variation in economic growth. Suggestions given to the Regional Government are to improve the quality of human resources through training programs, increasing access to education, and creating jobs.